The Role of Indigenous Communities in Turtle Breeding Activities, Skouw Yambe Village, Papua - Yuliana, Yuliana; Poli, Agustina Ivonne; Idris, Usman; Muttaqin, M. Zaenul (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
This study uniquely examines the role of indigenous communities in turtle conservation in Skouw Yambe Village, Jayapura City, Papua, by employing a descriptive qualitative approach. Unlike previous research, this study provides an in-depth analysis of local community conservation practices specifically focused on four turtle species: green turtle (Chelonia Mydas), hawksbill turtle (Eretmochelys Imbricata), loggerhead turtle (Caretta Caretta), and leatherback turtle (Dermochelys Coriacea). Unlike previous research that predominantly offered superficial, descriptive accounts of conservation activities, this study delves deep into the complex socio-ecological mechanisms that underpin community-driven environmental preservation. By applying qualitative approach, this study utilizes an integrated methodology of in-depth interviews and participatory observation. A total of nine informants were purposefully selected for this study, representing diverse perspectives within the indigenous community of Skouw Yambe Village. The study reveals a systematic traditional knowledge system for species identification and conservation practices, demonstrating how indigenous communities in Skouw Yambe Village effectively use intergenerational ecological knowledge to protect and manage local turtle populations The conservation process encompasses three critical stages: egg collection, incubation, and hatchling release, occurring between January and May each year. It demonstrates that turtle conservation in this location transcends mere species preservation, representing a manifestation of cultural values and environmental ethics. The community-based conservation model harmoniously synthesizes traditional ecological wisdom with modern conservation methodologies. The approach aims to prevent species extinction, protect coastal habitats, strengthen social cohesion, and empower local communities. The conservation initiative is supported by three fundamental components: high community awareness and participation, synergistic collaboration with government and non-governmental agencies, and conducive natural habitat conditions. Despite challenges such as plastic pollution and coastal erosion, the Skouw Yambe indigenous community has developed an adaptive conservation strategy. The study concludes by emphasizing the urgent need to recognize and support indigenous communities as ecosystem guardians, highlighting the potential of this community-based conservation model as a comprehensive reference for similar programs, while acknowledging the unique socio-ecological characteristics of each region.